NEW MIDDLE TRIASSIC POLLEN TAXA OF THE SAN RAFAEL BASIN, MENDOZA PROVINCE, ARGENTINA (Ameghiniana, 2021)
New pollen grains are described from diverse palynological assemblages recorded from the Quebrada de los Fósiles Formation, lower unit of the Puesto Viejo Group, San Rafael Basin (Mendoza, Argentina), southwestern Gondwana. Two new pollen genera, Mendozapollenites gen. nov. and Crackipollenites gen. nov., are proposed. Also, three new species, Mendozapollenites variabilis sp. nov., Angustisulcites hexagonalis sp. nov. and Crackipollenites polygonalis sp. nov., as well as Crackipollenites sp. A and an indeterminate monosaccate pollen (Form A), are fully described and illustrated. The microflora contains: high proportions of sphenophyte and lycophyte spores; true ferns and bryophyte spores as minor components; non-taeniate pteridosperm bisaccate pollen grains; taeniate monosaccate and bisaccate pollen, scarce monosulcate and inaperturate grains, among other less frequent gymnosperm pollen; and the co-occurrence of chlorococcalean algae and fungal spores. The sedimentation of the Quebrada de los Fósiles Formation took place during the Ladinian (Middle Triassic), as was confirmed by recent radiometric dating of ignimbrites from the base and the top of the main profile of the unit. Thus, this is the first unequivocal and unique microflora recorded at present for the Ladinian in South America.